Improving Medical Wellness with Halal and Thayyib Certification in Traditional Health Services: A Literature Review - Riskha Dora Candra Dewi; Suryono (Universitas Airlangga, 2025)
Halal and thayyib certifications are generally used to certify that food products adhere to Islamic rules.